Contingency Constrained VAr Planning Using Penalty Successive Conic Programming - Jabr,RA; Martins,N; Pal,BC; Karaki,S (IEEE Transactions on Power Systems, 2012)
This paper presents a new method for VAr planning under multiple operating scenarios, optimizing sizes and locations of new reactive compensation equipment to ensure that both the system voltage profile and voltage stability requirements are met. The approach is based on ${mbi L}_{1}$-norm regularization for finding a solution with minimum VAr installation sites and on the ${mbi L}_{2}$-norm penalty function for satisfying the multiple state constraints. The ${mbi L}_{2}$-norm penalty function is exact in the sense that a finite penalty parameter is required to establish equivalence with the VAr planning problem, thus avoiding numerical ill-conditioning. The solution is obtained from a successive conic programming algorithm which makes use of adaptive trust-region control. The results of the new method are compared with those of an optimal power flow-based program for VAr planning.